Изучение статической и динамической адсорбции-99м ТС на оксиде алюминия; Известия вузов. Физика; Т. 53, № 10-2 - Скуридин В. С. Виктор Сергеевич; Стасюк Е. С. Елена Сергеевна; Садкин В. Л. Владимир Леонидович; Чибисов Е. В. Евгений Владимирович; Рогов А. С. Александр Сергеевич; Чикова И. В. Ирина Владимировна (2010, 2010)
Заглавие с экрана